S75 High Dose Vitamin D Supplementation Improves Extravascular Lung Water Index and In-Vivo Treg and LL37 Responses Post-Oesophagectomy. (19th November 2012) - Dancer, RCA; Parekh, D; Martineau, AR; Perkins, GD; Thickett, DR
Abstract : Acute Lung Injury occurs in around 25% of patients post 2 stage oesophagectomy. We have previously shown that levels of 25-OH vitamin D are low in these patients and that those patients with the lowest levels of vitamin D are more likely to develop Acute Lung Injury post-operatively. In vitro, vitamin D has been shown to promote the differentiation of regulatory T cells (Treg) and the expression of LL37 (cathelicidin), an antimicrobial peptide. We have given 13 patients a one-off high dose vitamin D supplement 3–14 days prior to oesophagectomy. Numbers of circulating regulatory T cells were analysed both pre- and post-supplementation. Plasma levels of LL37 were measured by ELISA. Extravascular Lung Water Index (EVLWi) was measured pre-operatively, post-operatively and on the day following surgery. Changes in LL37 and EVLWi were compared with results from a cohort of patients (n=50) who had not been supplemented. Pre-operative vitamin D levels between the two groups were significantly different. The proportion of CD3+CD4+ T cells which were CD25+CD127loFoxP3+ increased post vitamin D supplementation (median pre vitamin D=5.8, median post vitamin D=7.3, p=0.028). Whilst levels of LL37 decreased post-operatively in the cohort who had not received vitamin D, levels were maintained in supplemented patients. Post-operative EVLWi measured lower than pre-operative values in patients receiving vitamin D supplementation. This contrasts with patients who did not receive vitamin D supplementation in whom an increase in EVLWi was seen. This difference persists on post-operative day 1, with a net increase being seen in patients who did not receive vitamin D and a net decrease in those who did (see table ). Conclusions: A stat high dose vitamin D supplement restored vitamin D levels in the week before oesophagectomy. This was associated with elevated circulating Treg levels in vivo and an increase in post-operative plasma LL37 expression suggesting the vitamin D supplementation was biologically active. Patients: receiving vitamin D had no perioperative increase in extravascular lung water compared to our historical cohort suggesting that vitamin D protects against alveolar epithelial damage perhaps in part due to effects on circulating Treg cells and anti-microbial peptide production.